Brand equity and the impact of social media marketing communication activities - Nur Amalina Hayati; Santi Delliana (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2023)
This study aims to determine the impact of social media marketing communications on brand equity. The research method used was quantitative, with purposive sampling serving as the sampling technique and a sample size of 96 people as the target population. Hypotheses are developed in quantitative data analysis by employing simple linear regression techniques. According to the findings, both categories include evaluating social media marketing communication activities and brand equity. According to the findings of the hypothesis testing, social media marketing communication activities have a significant impact on brand equity, with a strong category influence.